Native milk fat globule membrane damage : measurement and effect of mechanical factors in milk powder processing operations : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Food Technology of Massey University - Downey, Mark (Massey University, 2005)
The goal of this work was to measure native milk fat globule membrane (NMFGM) damage in a number of processing operations within the milk powder manufacturing process. Analysis of the literature showed that NMFGM damage was not well understood, particularly as caused by processing operations within factories. Reliable methods of measuring NMFGM damage were not available: current methods had limited scope or were qualitative in nature. In the highly mechanised dairy industry, damage to the NMFGM can lead to serious quality and financial losses owing to consequences such as lipolysis and creaming. The aims of this work were to develop new techniques for measuring NMFGM damage, and to use these in assessing the effects of a number of operations within the milk powder process. The majority of time was spent on developing two new tests, the selective lipolysis (SL1) test and the particle size zoning (PSZ) test. The SL1 test measures a chemical consequence of NMFGM damage, that is the production of free fatty acids (FFAs). The PSZ test measures a physical consequence of NMFGM damage, that is the change in the fat globule size distribution. Controlled experiments were used to measure NMFGM damage in process operations including pumping, agitation, preheating and evaporation. For these operations, variables such as shear, time, temperature, air inclusion and cavitation were investigated. Surveys of two industrial milk powder plants were also conducted. The results showed that the SL1 and PSZ tests were reproducible, sensitive enough to detect NMFGM damage in a number of process operations, and, together, could give a reasonably comprehensive picture of NMFGM damage. The results of pumping and agitation experiments were consistent with previous research, but were more comprehensive. The effects on measured NMFGM damage of the presence of separated fat in foam or as churned fat have hardly been described by previous workers. Results for the effects of preheating and evaporation on NMFGM damage are new, and challenged the findings of previous research. The need to improve the flexibility and practicality of the SL1 and PSZ tests, so they can he used as widely as possible to gain a comprehensive picture of NMFGM damage across many dairy processes, was identified. Studies should be made to connect the results of the particle size zoning and selective lipolysis tests with product quality and process efficiency data from industrial sites.
Keywords: Heat exchangers; Fouling; Dairy processing; Dried milk